1994
DOI: 10.1111/j.1558-5646.1994.tb05286.x
|View full text |Cite
|
Sign up to set email alerts
|

High Inbreeding Depression, Selective Interference Among Loci, and the Threshold Selfing Rate for Purging Recessive Lethal Mutations

Abstract: The evolutionary dynamics of recessive or slightly dominant lethal mutations in partially self-fertilizing plants are analyzed using two models. In the identity-equilibrium model, lethals occur at a finite number of unlinked loci among which genotype frequencies are independent in mature plants. In the Kondrashov model, lethals occur at an infinite number of unlinked loci with identity disequilibrium produced by partial selfing. If the genomic mutation rate to (nearly) recessive lethal alleles is sufficiently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
201
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(210 citation statements)
references
References 57 publications
7
201
2
Order By: Relevance
“…Preliminary results from a genetic study using seeds have shown that females do indeed have a selfing rate close to 0% in both the MP and OT populations (C. Deen, University of Georgia, and S.-M. Chang, unpublished data), similar to what is seen in many other gynodioecious species (e.g., Collin and Shykoff, 1993;Kohn and Biardi, 1995;Gibson and Wheelwright, 1996). However, use of mature seeds would underestimate the primary selfing rates (i.e., sefling rates for all fertilized ovules) if inbreeding depression is observed at stages prior to seed maturation, as shown in this study (Lande et al, 1994;Husband and Schemske, 1996). These values are on the low end of the selfing rate distribution even among outcrossing species (Vogler and Kalisz, 2001).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Preliminary results from a genetic study using seeds have shown that females do indeed have a selfing rate close to 0% in both the MP and OT populations (C. Deen, University of Georgia, and S.-M. Chang, unpublished data), similar to what is seen in many other gynodioecious species (e.g., Collin and Shykoff, 1993;Kohn and Biardi, 1995;Gibson and Wheelwright, 1996). However, use of mature seeds would underestimate the primary selfing rates (i.e., sefling rates for all fertilized ovules) if inbreeding depression is observed at stages prior to seed maturation, as shown in this study (Lande et al, 1994;Husband and Schemske, 1996). These values are on the low end of the selfing rate distribution even among outcrossing species (Vogler and Kalisz, 2001).…”
Section: Discussionsupporting
confidence: 85%
“…Lande et al (1994) showed theoretically that, when selfing rate is low, high rates of lethal mutations may kill nearly all selfed progeny and leave the population with only outcrossed progeny, a phenomenon called selective interference (Ganders, 1972). Lande et al (1994) showed theoretically that, when selfing rate is low, high rates of lethal mutations may kill nearly all selfed progeny and leave the population with only outcrossed progeny, a phenomenon called selective interference (Ganders, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…However, X. germanus is probably the species with the highest degree of continuous sibling mating in which inbreeding effects ever have been examined. Theoretical work has shown that purging may not occur until a critical threshold selfing/inbreeding rate is reached (Lande et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, with segregation of partially-dominant or recessive deleterious alleles, male maintenance is favored because it mitigates inbreeding depression [1], [5], [24], [25]. In populations without genetic diversity however, selfing is expected to be more efficient at purging new deleterious alleles than outcrossing since more homozygotes are readily produced [26], [27], [28]. In C. elegans inbreeding depression should not however explain male maintenance because crosses among wild isolates have failed to show it [11], [29], and males have only a minor role in buffering partially-dominant deleterious mutations in laboratory populations [30], [31] (but see [2]).…”
Section: Introductionmentioning
confidence: 99%